Design of a Solar Powered Precision Irrigation System. - Othieno John Wangara (Kabale University, 2023)
Agriculture requires sunlight, fertile soil and water for high quantity and quality produce. However in Africa especially in sub-Sahara Africa this has been high hindered by unreliable levels of rainfall as result of it having too much sun heat (desert) which intern calls for irrigation. Irrigation generally is the controlled application of water for agricultural purposes. Globally, 70% of water use is applied in irrigation of crops, making irrigation the largest consumptive user of fresh water. Over 80% of freshwater withdrawals in developing countries is applied in irrigation. Irrigated agriculture provides 40% of the world's food from less than 20% of the cultivated area highlighting the importance of irrigation in global food security. Improved soil moisture and plant sensors, and developing self-learning crop simulation frameworks that can be applied to evaluate adaptive decision support strategies related to irrigation. However traditional irrigation systems use large volumes of water and energy requirement to run. This in tum results into large energy and water wastage as most of the water is not used to irrigate the plant. Statistics show that Sprinklers waste 30 to 50 percent of water through evaporation, runoff and apply water where it isn't needed and other factors. Flood irrigation wastes between 40 to 65 percent of the water due to factors like overtopping, runoff in the drain, rat holes in the canal bunds, evaporation from the water surface among others. [ 1] This is also accompanied by the fact that most used energy sources are fuel energy since hydro electrical energy (HEP) is not extended in most rural areas where actual agriculture is practiced and even the few rural areas having the hydroelectric power face frequent black outs thus leaving H.E.P unreliable thus fossil energy source the only alternative. These increase farming cost since the current irrigation systems use fuel energy and also have negative impacts on the environment through air, water and land pollution and its effects. Hence need to use environmentally friendly solar powered precision irrigation machine. [2] This study seeks to design an irrigation system that supplies just enough amount of water needed to meet the irrigation water requirement of the plants and using renewable energy in form of solar energy.